2020
DOI: 10.1177/2059204320957273
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Exploration of the Stability of Music- and Photo-Evoked Autobiographical Memories in People with Alzheimer’s and Behavioral Variant Frontotemporal Dementia

Abstract: Music evoked autobiographical memories (MEAMs) occur in people with Alzheimer’s dementia (AD), but there is limited study of such memories in people with other dementia types such as behavioral variant frontotemporal dementia (Bv-FTD). Furthermore, there has been no study of the integrity of such memories over time, and scarce comparison with other memory cues such as photos. Our aim was to address this current gap in our knowledge and to characterize MEAMs and photo-evoked autobiographical memories (PEAMs) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 42 publications
(83 reference statements)
0
17
0
2
Order By: Relevance
“…“It is extraordinary how music sends one back into memories of the past.” This quote from author Amantine Lucile Aurore Dupin (known as George Sand) exemplifies the widespread belief that music is somehow “special” in its ability to conjure up memories and associated feelings from our lives. This idea has been partially supported by research showing that music can evoke qualitatively different autobiographical memories than other types of retrieval cues in both healthy and clinical populations (Baird et al, 2018, 2020; Belfi et al, 2016, 2020; El Haj et al, 2012; Jakubowski et al, 2021; Zator & Katz, 2017). The present work aims to critically examine the extent to which these differences between music-evoked autobiographical memories (MEAMs) and other autobiographical memories emerge in healthy adults, specifically by taking into account emotional features of the retrieval cues as a potential factor that may drive differences in memory accessibility and content.…”
Section: Comparing Autobiographical Memory Cuesmentioning
confidence: 97%
“…“It is extraordinary how music sends one back into memories of the past.” This quote from author Amantine Lucile Aurore Dupin (known as George Sand) exemplifies the widespread belief that music is somehow “special” in its ability to conjure up memories and associated feelings from our lives. This idea has been partially supported by research showing that music can evoke qualitatively different autobiographical memories than other types of retrieval cues in both healthy and clinical populations (Baird et al, 2018, 2020; Belfi et al, 2016, 2020; El Haj et al, 2012; Jakubowski et al, 2021; Zator & Katz, 2017). The present work aims to critically examine the extent to which these differences between music-evoked autobiographical memories (MEAMs) and other autobiographical memories emerge in healthy adults, specifically by taking into account emotional features of the retrieval cues as a potential factor that may drive differences in memory accessibility and content.…”
Section: Comparing Autobiographical Memory Cuesmentioning
confidence: 97%
“…were presented in both settings, with notably more autobiographical memories been recalled in the museum setting (Miles et al, 2013). Finally, sensory evoked autobiographical memories seem to be particularly benefited from cues derived from one's young adulthood (e.g., Baird et al, 2018;Baird et al, 2020;Rasmussen et al, 2021). These studies provide evidence that autobiographical memory performance might benefit from ecologically valid methods.…”
Section: Autobiographical Memorymentioning
confidence: 74%
“…Indeed, deteriorated autobiographical memory performance in people with dementia has been demonstrated by the majority of studies, with findings showing a diminished capacity to recall and produce specific past personal episodes (Barnabe et al, 2012;El Haj et al, 2017;El Haj & Antoine, 2020;Irish et al, 2018 ;Irish et al, 2011b;Benjamin et al, 2015;De Simone et al, 2016;Donix et al, 2010;Baird et al, 2020;Kirk & Berntsen, 2018a;Kirk & Berntsen, 2018b;Leyhe et al, 2009;Liechti et al, 2019;El Haj et al, 2022a;Meulenbroek et al, 2010;Viard et al, 2013;Rauchs et al, 2013;Philippi et al, 2012;Philippi et al, 2015;Baird et al, 2018;Berntsen et al, 2022;Muller et al, 2016;Caddell & Clare, 2012;El Haj et al, 2015d;El Haj & Allain, 2020;El Haj & Antoine, 2017b;Addis et al, 2009;El Haj et al, 2019b;El Haj et al, 2020b;El Haj et al, 2016;Jetten et al, 2010;Martinelli et al, 2013 ;Rathbone et al, 2019;Maguire et al, 2010). In one case study, autobiographical memory performance progressed from intact to significantly deteriorated within 3 years (Maguire et al, 2010), while in another longitudinal study autobiographical memory performance was mostly the same in a 1-year follow-up, with specific disruptions in performance of personal semantic memory (Irish et al, 2018).…”
Section: Autobiographical Memorymentioning
confidence: 99%
“…Baird, Gelding, et al (2020) had a similar design to Baird et al (2018), and investigated the stability of the performance 6 months apart in seven participants with AD, six participants with bv‐FTD, and nine healthy age‐matched controls. They found that the same stimuli tended to evoke memories at both points, with no differences in controls and AD.…”
Section: Resultsmentioning
confidence: 99%